Improved isolation of carbapenem-resistant Enterobacterales on selective-differential media extending the incubation time: an approach to strengthen the antimicrobial surveillance from rectal swabs. (November 2022) - Piatti, G.; Schito, A.M.; Vitale, A.; Bruzzone, M.; Ceppi, M.
Summary: Background: Surveillance of carbapenem-resistant Enterobacterales (CRE) carriers is the first measure of hospital infection control. Screening of CRE carriage can be assessed through culture and molecular techniques, each with specific properties of turnaround-times, sensitivity and specificity. Methods: This was a prospective study in a 1200-bed university hospital in Genoa, Italy, where CRE screening is performed analysing cultures from rectal swabs. Our 18-months intervention was to extend the incubation time of the corresponding plates from 48 to 288 h, after reporting negative tests, to evaluate the possible impact on the cultures. Findings: A total of 362 patients giving 19, 278 swabs and corresponding plates were included. After baseline incubation, plate positivity was 3%, while after the overall lengthened times it was 3.7%. Extended incubation was associated with change in the relative frequency of the most represented species. In particular, we observed reduced presence of total and resistant Klebsiella pneumoniae strains ( P <0.001) and increased presence of Enterobacter cloacae complex, total and sensitive ( P <0.001). By extending incubation time, a reduced frequency of overall Enterobacterales strains with high resistance to ertapenem (MIC ≥4 mg/L) was also found ( P =0.005), particularly that of K. pneumoniae ( P <0.001), while the presence of E. cloacae complex increased among organisms with low resistance levels to ertapenem ( P <0.001). Conclusions: Extending the incubation time of the cultures increased the number of CREs grown, and expanded the bacterial scenario of rectal colonization through the recovery of poorly resistant strains and otherwise undetected species.